MECHANISM TASTE AND AROMA - Геник, С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The feelings of taste comes not only from nose or mouth, their posterior wall, but from taste ceels in intestines. Taste feelings of what we eat is formed by our mother, our family, our impressions, from child hood as well as the room where we are eating, the plates in which the food is served and the frieds eating side by side. This processis psychophysiological as well as chemical. The feeling of hunger and seeking for food plasure can effect further more than taste bulbs. Incompatible ingrediens, that contain a lot of aromatic chemicals combined together create a wonderful taste. Based on this fact scientists create. The Mapof Flavors. The reseaches performing nowadays investigate how the food continues changing the world by changing our selves , starting from unexpected reasons of obesity and new ideas of enlargment of food industry.